Growth analysis of two bean cultivars under irrigation in no tillage and the conventional tillage - Urchep, Mário Artemio; Rodrigues, João Domingos; Stone, Luis Fernando (Pesquisa Agropecuaria Brasileira, 2000)
This work was carried out with the objective of evaluating, through the growth analysis, the effects of no tillage, and the conventional tillage on the development of two common bean (Phaseolus vulgaris L.) cultivars, sown in two different row spacings, under a center-pivot irrigation system. The experiment was carried in 1994, at Senador Canedo, Goiás State, Brazil, located at 16° 41' South, 49° 16' West, and 741 m above sea level. The experimental design was an entirely randomized with split-split-plot and eight treatments. For evaluating leaf area and dry matter production (Wt), ten samples were collected at seven days intervals, randomly taking three plants, replicated two times. The growth analysis showed that, in the no tillage system, the bean plant increased the Wt, the leaf area index, the crop growth rate, the relative growth rate, the net assimilation rate, and the leaf area duration, and decreased the leaf area ratio. The Aporé cultivar was better than Safira, without row spacing effect. The growth analysis was shown as an adequate tool for evaluating the development of the common bean plant.